2001
DOI: 10.1051/0004-6361:20010077
|View full text |Cite
|
Sign up to set email alerts
|

The Be/X-ray transient 4U 0115+63/V635 Cassiopeiae

Abstract: Abstract. We present multi-wavelength long-term monitoring observations of V635 Cas, the optical counterpart to the transient X-ray pulsar 4U 0115+63. The evolution of emission lines and photometric magnitudes indicates that the Be star undergoes relatively fast (∼3 − 5 yr) quasi-cyclic activity, losing and reforming its circumstellar disc. We show that the general optical, infrared and X-ray behaviour can be explained by the dynamical evolution of the viscous circumstellar disc around the Be star. After each … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 27 publications
5
90
0
Order By: Relevance
“…3.1, the rotational velocities given in Table 3 and the peak separation of the first available asymmetric profile after the disc loss, namely, Δ peak = 220 km s −1 (X-Per, Clark et al 2001), Δ peak = 305 km s −1 (4U 0115+63, Negueruela et al 2001), we find that the disc must reach a radius of ∼4 R * for the onset of the V/R variability. Virtually the same value is derived from Fig.…”
Section: Discussionmentioning
confidence: 62%
“…3.1, the rotational velocities given in Table 3 and the peak separation of the first available asymmetric profile after the disc loss, namely, Δ peak = 220 km s −1 (X-Per, Clark et al 2001), Δ peak = 305 km s −1 (4U 0115+63, Negueruela et al 2001), we find that the disc must reach a radius of ∼4 R * for the onset of the V/R variability. Virtually the same value is derived from Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Rappaport et al (1978) determined the binary's main parameters: orbital period ∼ 24.3 days, orbital eccentricity 0.34, and projected semimajor axis of the relativistic object axsini ∼ 140 light seconds (see also Tamura et al, 1992;Lutovinov et al, 1994, for an improvement of the parameters). The optical observations of the star V635 Cas Kholopov et al, 1981), which is the normal stellar companion of the X-ray source 4U 0115+63, performed by Negueruela and Okazaki (2001) allowed the star's spectral type to be improved, B0.2Ve, and the binary's distance to be estimated, 7-8 kpc. The X-ray pulsar 4U 0115+63 is unique in its spectral characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al (1978) showed that m = 1 modes in nearly Keplerian disks, which are neutral if viscosity is neglected, become overstable when viscous effects are taken into account. The growth rate is proportional to α (see also Negueruela et al 2001).…”
Section: Disk Structurementioning
confidence: 99%